2006
DOI: 10.20870/oeno-one.2006.40.2.878
|View full text |Cite
|
Sign up to set email alerts
|

Global survey of the microbial ecosystem during alcoholic fermentation in winemaking

Abstract: The alcoholic fermentation is a crucial winemaking step. Its failure is problematic. In spite of several studies to understand and elucidate these problems wine global microbial ecology has never been considered. Using conventional microbiological methods and sensitive molecular tools we monitored the alcoholic fermentations of different red grape varieties in several cellars located in Bordeaux area. These observations were made during three successive vintages in different oenological conditions. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…These conditions are created once alcoholic fermentation is completed and traces of residual sugars allow them to proliferate more easily. Malolactic fermentation (MLF) and ageing in used barrels have therefore been recognised as the most critical stages of wine production for Brettanomyces/Dekkera contamination (Chatonnet et al, 1992(Chatonnet et al, , 1995Fugelsang et al, 1993;Licker et al, 1998;Renouf et al, 2006b;Suárez et al, 2007). During MLF, Brettanomyces/Dekkera spp.…”
Section: Occurrence and Distribution During Winemakingmentioning
confidence: 99%
“…These conditions are created once alcoholic fermentation is completed and traces of residual sugars allow them to proliferate more easily. Malolactic fermentation (MLF) and ageing in used barrels have therefore been recognised as the most critical stages of wine production for Brettanomyces/Dekkera contamination (Chatonnet et al, 1992(Chatonnet et al, , 1995Fugelsang et al, 1993;Licker et al, 1998;Renouf et al, 2006b;Suárez et al, 2007). During MLF, Brettanomyces/Dekkera spp.…”
Section: Occurrence and Distribution During Winemakingmentioning
confidence: 99%
“…They were also known to intervene during the first step of the winemaking (Renouf et al, 2006a). It was also the case of the Candida stellata, Candida cantarelli, Mestchnikowia fructicola and Pichia anomala yeast species (Clemente-Jimenez, 2004;Renouf et al, 2006e).…”
Section: Pcr-dgge Analysis On the Berry Surfacementioning
confidence: 99%
“…Before fermentations, yeast and bacteria species Other works reported that these species and their growth in must could be influenced by oenological practices such as the sulphite dioxide addition (Ciani et Pepe, 2002), the use of initial cold maceration (Renouf et al, 2006e), the addition of commercial strain starter (Raspor et al, 2002), and, also by the oxygenation (Strehaiano, 1990) and chemical parameters of must (Bely et al, 1990;Alexandre and Charpentier, 1998).…”
Section: Pcr-dgge Analysis During the Winemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…These faults cause large economic losses 13 . In the last fifteen years, studies regarding these microorganisms have multiplied in a significant way 3,6,7,20,31,35 and indicate a desire to understand the behaviour of Brettanomyces and to prevent or at least control its development in the winemaking process.…”
Section: Introductionmentioning
confidence: 99%